1993
DOI: 10.1063/1.108596
|View full text |Cite
|
Sign up to set email alerts
|

Reflection high energy electron diffraction intensity oscillations during the growth by molecular beam epitaxy of GaAs(110) films

Abstract: Reflection high energy electron diffraction (RHEED) intensity oscillations are reported for GaAs growth by molecular beam epitaxy (MBE) on singular GaAs (110) substrates. The behavior is quite different from that observed for any other system involving a singular surface and elemental sources, in that the oscillation period is a function of temperature, flux ratio, and growth time. The results are discussed in terms of possible growth modes and relative adatom populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…3 By careful consideration of the diffraction and growth conditions, the oscillatory behavior of the specular RHEED beam is explained in terms of a temporal variation in the surface step edge density during growth. 6 STM studies support the layer-by-layer growth mechanism with the temporal variation in surface step density giving rise to the RHEED oscillations. 5 In general, RHEED intensity oscillations can only be obtained for the ͑110͒ surface when using a relatively low substrate temperature, a low growth rate, and a high As/Ga flux ratio.…”
Section: Introductionmentioning
confidence: 55%
“…3 By careful consideration of the diffraction and growth conditions, the oscillatory behavior of the specular RHEED beam is explained in terms of a temporal variation in the surface step edge density during growth. 6 STM studies support the layer-by-layer growth mechanism with the temporal variation in surface step density giving rise to the RHEED oscillations. 5 In general, RHEED intensity oscillations can only be obtained for the ͑110͒ surface when using a relatively low substrate temperature, a low growth rate, and a high As/Ga flux ratio.…”
Section: Introductionmentioning
confidence: 55%
“…3 However, with a suitable choice of growth parameters, in particular a relatively low substrate temperature, low growth rate, and a high As/Ga flux ratio, reflection high-energy electron diffraction ͑RHEED͒ studies showed that oscillations in the specular beam intensity could be obtained which indicate two-dimensional layer-by-layer growth. 4 This growth mode was recently confirmed by scanning tunneling microscopy ͑STM͒, with the temporal variation in surface step density being responsible for the specular RHEED oscillations. 5 When growth is carried out under more As-rich conditions, RHEED oscillations show a doubling of the period.…”
mentioning
confidence: 70%
“…These conditions were plotted to produce a phase map of the growth conditions for which specular intensity oscillations were recordable. RHEED oscillations were obtained over a much wider range of growth conditions when using As 2 compared to growth using As 4 . It is shown that this is related to the very different incorporation coefficients of the two arsenic species and reflects the requirement of a high arsenic adatom concentration in order to maintain the 1:1 stoichiometry of the nonpolar ͑110͒ surface.…”
mentioning
confidence: 99%
“…The standard approach to the epitaxial growth of ZnSe on (001) GaAs is well-documented: 100 [14,15]). Under Se-rich conditions (Se/Zn BEPR=2), the RHEED shows 2D growth during epitaxy.…”
mentioning
confidence: 99%